Penerapan Metode Pembelajaran STEAM untuk Meningkatkan Keterampilan Berbicara pada Mata Pembelajaran Bahasa Indonesia Di Sekolah Dasar - Vernita, Ninda; Novianti, Novianti; Sujiono, Sujiono (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study investigates the efficacy of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in enhancing speaking skills among fifth-grade students in Indonesian language instruction at SD Negeri 1 Pokoh Kidul. Employing classroom action research based on the Kemmis and McTaggart model, the study involved 29 students across two cycles of planning, action, observation, and reflection in the 2024/2025 academic year. Data were collected through observations, interviews, tests, and documentation, and analyzed using qualitative and quantitative methods. Findings reveal a significant improvement in speaking skills: the pre-cycle mean score of 68.69 (27.59% mastery) increased to 74.66 (75.86%) in Cycle I and 80.34 (89.66%) in Cycle II. Project-based activities, including group discussions and museum guide simulations, fostered confidence, fluency, and vocabulary enrichment. The STEAM approach proved effective in creating an engaging, contextual learning environment to develop elementary students’ speaking proficiency.